Computer Modeling System of the Industrial Diesel Fuel Catalytic Dewaxing Process; Chemical Engineering & Technology; Vol. 44, iss. 6 - Belinskaya N. S. Natalia Sergeevna; Ivanchina E. D. Emilia Dmitrievna; Dolganov I. M. Igor Mikhailovich; Belozertseva N. E. Nataljya Evgenjevna; Afanasjeva D. A. Darjya Aleksandrovna (2021, 2021)
Title screen